Fluor kumur program on students in the garden school of park forest private village through empowerment Posyandu as dental health care (Talenta Publisher, 2019)
Until now, cavities (caries) is still a dental and oral health problem that requires the attention of health workers. In some countries, the prevalence of dental disease has been reported to have declined, but from Riskesdas data the prevalence in Indonesia is still quite high at 72.86%. The WHO Global Oral Health Program (GOHP) advises countries in the world to develop policies for the prevention of dental and oral diseases and the promotion of dental and oral health. especially for school children and teenagers. One form of effort undertaken is to carry out a Fluorine rinse program in the Taman Siswa village of the Embassy of Silau Village by empowering Posyandu cadres to become dental health cadres. It is expected that this program can increase public awareness, especially the school community, to maintain oral and dental health so that optimal oral and dental health can be achieved for school children.